Communicative Methodology: Contributions to Social Impact Assessment in Psychological Research - Redondo-Sama, Gisela; Díez-Palomar, Javier; Campdepadrós, Roger; Morlà-Folch, Teresa (Frontiers in Psychology, 2020)
Recent advancements in the social impact assessment of science have shown the diverse methodologies being developed to monitor and evaluate the improvements for society as a result of research. These assessment methods include indicators to gather both quantitative and qualitative evidence of the social impact of science achieved in the short, medium and long terms. In psychology, the impact of research has been mainly analysed in relation to scientific publications in journals, but less is known about the methods for the social impact assessment of psychological research. Impact assessment in the domains of educational psychology and organizational psychology presents synergies with bottom-up approaches that include the voices of citizens and stakeholders in their analyses. Along these lines, the communicative methodology (CM) emerges as a methodology useful for the communicative evaluation of the social impact of research. Although the CM has widely demonstrated social impact in the social sciences, less is known about how it has been used and the impact achieved in psychological research. This article unpacks how to achieve social impact in psychology through the CM. In particular, it focuses on the theoretical underpinnings of the CM, the postulates linked to psychological research and some key actions for the implementation of the CM in relation to the design of advisory committees, working groups and plenary meetings in research. Furthermore, it shows how the CM has been implemented in illustrative cases in psychological research. The article finishes with a conclusion and recommendations to further explore the ways in which the CM enables the social impact of research in psychology.